Implementation of the Problem Base Learning Model combined with E-STEM Based Student Worksheets on Learning Outcomes and Self Efficacy on Environmental Pollution Materials - Cut Putri Amalya; Wiwit Artika; Safrida Safrida; Cut Nurmaliah; Muhibbuddin Muhibbuddin; M. Syukri (Postgraduate, University of Mataram, 2021)
The learning process has not emphasized the development of skills; this is because in learning students tend to memorize concepts so that learning outcomes and self-efficacy are not trained optimally. The formulation of the problem in this study is: is there a difference in learning outcomes and student self-efficacy between the use of the Problem Base Learning model combined with the E-STEM-based Student Worksheet with the Problem Base Learning model on environmental pollution material at MAN Banda Aceh? This research is quantitative with an experimental research approach. The research design used was pretest-posttest control group design. The population of this study was all students of class X MAN 3 Banda Aceh, totaling 84. The sampling technique used a total sampling of 84 students. The instrument used to measure learning outcomes is multiple choice questions using 30 questions and self-efficacy is measured using a questionnaire. Data analysis of learning outcomes and self-efficacy of students using independent sample t-test at a significant level of 0.05. The results showed that there were differences in student learning outcomes and self-efficacy after applying the Problem Base Learning model combined with the E-STEM-based Student Worksheet on environmental pollution materials at MAN Banda Aceh